Evaluación del incremento de la demanda de energía en los transformadores del alimentador IV centenario, por la entrada de nuevas cargas residenciales. - Rojas Vivanco, Luis Gabriel (2015)
This presents work shows the study of induction stoves income South Regional Utility primary feeder IV Centenario SA EERSSA in Loja city. For analysis of the increase in demand, we use software (distribution studies) that was published in the National University of Loja in order to analyze the input electromagnetic induction cookers distribution channels used. The study was presented in three stages, the first based on the provision of MEER in office no. MEER-SDCE-2014-0203-OF, in which the number of stoves are detailed input by distributor in the country, and determines that the city of Loja enter 143.765 stoves in three years, considering the number of stoves per year is estimated to stoves input transformer is dependent on the number of residential users, sharing stoves in three years with 12% , 55% and 33% respectively. For the second scenario is hypothesized that the entry of induction cooking is done in two years for which 12% of stoves for the first year and 88% for the second year. For scenarios 1 and 2 it is used 1.6 kVA demand for induction stoves that comes standard in the Edis software for the analysis of the third stage is used 0.448 kVA demand corresponding to the maximum diversified demand curve is adopted Westinghouse for induction cookers and considers the input induction stoves is similar to scenario 1. An analysis of the feeder IV Centenario is obtained in scenarios 1 and 2, the 73.39% of the installed at this time overloaded transformers, the maximum projected for 2024 in both scenarios demand increases by 5 times the current demand in the Scenario 3 overload the 59.63% of installed processing centers and high demand for 2024 is 2.43 times greater than current demand. The input schedule induction cookers for the three scenarios shown in Table 1, the percentages are dependent on the number of residential users each containing processing center.